How psychosocial factors affect well-being of practice assistants at work in general medical care?: a questionnaire survey - Götz, Katja; Berger, Sarah; Gavartina, Amina; Zaroti, Stavria; Szecsenyi, Joachim (BMC family practice, 2015)
Background: Well-being at work is an important aspect of a workforce strategy. The aim of the study was to explore and evaluate psychosocial factors and health and work-related outcomes of practices assistants depending on their employment status in general medical practices. Methods: This observational study was based on a questionnaire survey to evaluate psychosocial aspects at work in general medical practices. A standardized questionnaire was used, the Copenhagen Psychosocial Questionnaire (COPSOQ). Beside descriptive analyses linear regression analyses were performed for each health and work-related outcome scale of the COPSOQ. Results: 586 practice assistants out of 794 respondents (73.8 %) from 234 general medical practices completed the questionnaire. Practice assistants reported the highest scores for the psychosocial factor ‘sense of community’ (mean = 85.9) and the lower score for ‘influence at work’ (mean = 41.2). Moreover, practice assistants who worked part-time rated their psychosocial factors at work and health-related outcomes more positively than full-time employees. Furthermore, the two scales of health related outcomes ‘burnout’ and ‘job satisfaction’ showed strong associations between different psychosocial factors and socio-demographic variables. Conclusions: Psychosocial factors at work influence well-being at work and could be strong risk factors for poor health and work-related outcomes. Effective management of these issues could have an impact on the retention and recruitment of health care staff.
Gesehen am 29.06.2020